Brain Computer Interface (BCI) Machine Learning Process: A Review - Shofi Afif Hanafi; Hisyam Bin Abdul Rahman; Dwika Ananda Agustina Pertiwi; Much Aziz Muslim (Journal of Electronics Technology Exploration, 2023)
The abstraction of Brain Computer Interface (BCI) is a communication and control system that translated human mind thoughts into real-world interaction without any use of neural pathways and muscles. BCI is used as a tool to help person that suffered from impairment to be able do their daily activities independently. In general, BCI process its signal through several process such as pre-processing, and classification. However, providing information of pre-processing and classification process is barely found. Therefore, in this review paper we present the various pre-processing and classification methods that used in the BCI system application.